Serial Case of Acute Pulmonary Embolism: Different Therapies based on Different Patient Profiles - Ahmad, Ilzy Jum; Mappangara, Idar; Muzakkir, Akhtar Fajar (Jambura Medical and Health Science Journal, 2025)
Pulmonary embolism (PE) is the third leading cause of cardiovascular death. The high mortality rate prompted an analysis of these three-case series to evaluate various treatment options. Case I, a 66-year-old woman with acute shortness of breath and a history of EVLA because of chronic venous insufficiency in the left leg. She had comorbid of hypertension. She was diagnosed with massive PE with unstable hemodynamics. Catheter-directed thrombolysis (CDT) using Alteplase showed significant improvement within 24 hours. Case II, a 45-year-old woman with dyspnea de effort for one month and a 5-year history of hypertension. MSCT angiography showed a significant PE with partial stenosis, pulmonary hypertension, and a bidirectional atrial septal defect. Combination therapy with heparin, sildenafil, and furosemide had been provided but the patient had sudden cardiac death. Case III, a 36-year-old woman with dyspnea on effort after the delivery. Initial echocardiography showed right atrial and left ventricular thrombi. On the second day of treatment, clinical deterioration occurred due to thrombus migration to the pulmonary artery, confirming the diagnosis of acute PE. CDT therapy was performed. A 24-hour evaluation revealed persistent occlusion of pulmonary artery, leading to percutaneous transluminal angioplasty, which successfully restored blood flow. This case series report emphasizes the importance of risk-based therapy, including CDT for high-risk PE, anticoagulation for intermediate- to low-risk PE, and hemodynamic support in cases of shock. Keywords: Clinical deterioration, heparin, pulmonary embolism, thrombolytic therapy, tissue plasminogen activator